The Effect of NaCl Reduction and Replacement on the Growth of Listeria Monocytogenes in Broth, Cooked Ham and White Sauce. Issue 1 (25th January 2013) - Samapundo, Simbarashe; Anthierens, Tom; Ampofo‐Asiama, Jerry; Xhaferi, Ramize; Van Bree, Ilse; Szczepaniak, Slawomir; Goemaere, Olivier; Steen, Liselot; Dhooge, Marieke; Paelinck, Hubert; Devlieghere, F.
Abstract The growth‐inhibiting effects of simple and commercial salt replacers on the growth of Listeria monocytogenes were determined in broth at 7C. The divalent chlorides, CaCl2 and MgCl2, had the largest antilisterial activities at equivalent water phase concentrations or molalities followed by NaCl ≈ KCl and MgSO4 in decreasing order of antilisterial effect. Additional antilisterial activities other than their water activity depressing effects were observed for CaCl2 and MgCl2. Challenge tests performed on cooked ham and white sauce showed that reduction of NaCl levels by ≤28 and 33%, respectively, did not affect the stability of these products to L. monocytogenes. It can be concluded from the study that changes in the stability to L. monocytogenes are most likely to occur when NaCl is fully reduced and/or replaced or partially replaced by either CaCl2 (increased stability) or MgSO4 (reduced stability). Practical Applications The association of high dietary NaCl levels to hypertension and cardiovascular diseases has led to concerted efforts in the food industry to reduce NaCl levels. To date, several studies have been performed, which have focused primarily on addressing the sensorial, technological and shelf life aspects, with far less emphasis being placed on the food safety aspects. The results of this study provide much needed insight into the potential food safety consequences of reduction and/or replacement of NaCl in food products.